2022
DOI: 10.3103/s1067821222030117
|View full text |Cite
|
Sign up to set email alerts
|

The Viscosity of Molten Salts Based on the LiF–BeF2 System

Abstract: Аннотация: Методом ротационной вискозиметрии с использованием высокотемпературного реометра FRS 1600 («Anton Paar», Австрия) получены температурные зависимости динамической вязкости расплавов солей фторидов лития и бериллия, рассматриваемых в качестве кандидатных составов топлива и теплоносителя для жидкосолевого реактора (ЖСР) сжигателя долгоживущих актинидов из отработавшего ядерного топлива водо-водяного энергетического реактора 1000/1200. Применительно к промежуточному и топливному контурам ЖСР исследованы… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…According to the last NVT configuration, the positions of Li or Be are manually exchanged with La to overcome the possible dynamic energy barriers while enriching sampling configurations. These new configurations are named by the number of Li (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and Be (1-6), which are simulated by repeating the above NPT-NVT process, respectively.…”
Section: Fpmd Simulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the last NVT configuration, the positions of Li or Be are manually exchanged with La to overcome the possible dynamic energy barriers while enriching sampling configurations. These new configurations are named by the number of Li (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and Be (1-6), which are simulated by repeating the above NPT-NVT process, respectively.…”
Section: Fpmd Simulationsmentioning
confidence: 99%
“…According to eqn (6), the viscosity of pure Flibe at 823 K is calculated as 9.08 cP, lower than that of pure Flibe (11.5 cP for 66 LiF: 34 BeF 2 ), but consistent with that of 73 : 27 Flibe (9.10 cP). 3 The experimental viscosity of molten Flibe with the addition of lanthanide compounds is missing, but it can be confirmed that the introduction of high valence ions will increase the viscosity of the blank salt. 58 In addition, structural factors or specific ion interactions that influence the viscosity trend will be further elaborated in Section 3.3. , where all the g(r) curves quickly converge to unity with a cutoff distance of 7 Å, indicating that these simulation cells are large enough to accommodate a system that shows intermediate range Coulomb interactions.…”
Section: Be-bementioning
confidence: 99%
See 1 more Smart Citation
“…All in all, there are six variations including very high-temperature reactor (VHTR), sodium-cooled fast reactor (SFR), supercritical-water-cooled reactor (SCWR), gascooled fast reactor (GFR), lead-cooled fast reactor (LFR) and molten salt reactor (MSR). [1][2][3][4][5] Among the advantages of the MSR, we shall mention low vapor pressures at high temperatures ranging from 773 to 1023 K, which is characteristic for molten salts; such media as fluoride [6][7][8][9][10] and chloride 10,11 mixtures of alkali metals are well known by their high specific thermal capacity per the volume unity; molten salts are radiation resistant compounds that do not react with fuel in emergency case; the requirement for fuel preparation are minimal and the molten salt nuclear reactor design allows extracting the fission products and supplying fissile materials during the reactor operation. 12 Molten fluoride and chloride mixtures media proved to be more cost-efficient than aqueous media, as degradation processes caused by the process of water radiolysis are eliminated and the total exposure time required for processing of spent nuclear fuel with high burnup is reduced.…”
mentioning
confidence: 99%